2015
DOI: 10.4187/respcare.03838
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Convex-Probe Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration: A Multi-Center Retrospective Study

Abstract: BACKGROUND: Infrequent serious complications of convex-probe endobronchial ultrasoundguided transbronchial needle aspiration (EBUS-TBNA) have been reported. The aim of this study was to assess serious complications related to convex-probe EBUS-TBNA and to determine the complication rate in a large group of subjects. METHODS: In this retrospective study, a 15-item questionnaire on features of cases with EBUS-TBNA complications was sent to experienced bronchoscopists performing convex-probe EBUS-TBNA at 3 pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 23 publications
0
63
0
3
Order By: Relevance
“…According to a Japanese nationwide survey, the infectious complication rate of EBUS-TBNA was 0.19%4. A recent study of 3,123 cases undergoing the procedure reported infectious complications in 0.16%5. Serious complications such as mediastinal abscess, pneumomediastinum, empyema, pericarditis, sepsis, and intramural hematoma have been described in case reports678.…”
Section: Introductionmentioning
confidence: 99%
“…According to a Japanese nationwide survey, the infectious complication rate of EBUS-TBNA was 0.19%4. A recent study of 3,123 cases undergoing the procedure reported infectious complications in 0.16%5. Serious complications such as mediastinal abscess, pneumomediastinum, empyema, pericarditis, sepsis, and intramural hematoma have been described in case reports678.…”
Section: Introductionmentioning
confidence: 99%
“…However, the puncture of LNs with low-density areas did not elevate the frequency of postbronchoscopy fever in this study. The risk of infectious complications after puncturing a cystic lesion was demonstrated in a past report [31]. Patient selection, thus, could be more important in preventing infectious adverse events.…”
Section: Discussionmentioning
confidence: 94%
“…One of secondary outcome was preventive effect of serious infectious complications by prophylactic antibiotics in this preliminary study, and those kind of infectious events did not occur. Recent large multicenter-retrospective studies have shown that serious infectious complications after EBUS-TBNA are very rare (0.16%-0.19%) [15,31]. It was unclear whether prophylactic antibiotics had been used to treat patients in past reviews; nevertheless, precautions against such rare complications may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, three studies reported having observed agitation, cough, and presence of blood at the puncture site (12). In another retrospective study analyzing 3123 patients undergoing EBUS, the complication rate was found to be low at 0.16% that included pneumomediastinum with empyema, mediastinal abscess, fever lasting longer than 24 h, infection of a bronchogenic cyst, and pericarditis (7). These data suggest that EBUS-TBNA is a safe procedure when compared to mediastinoscopy, with an associated morbidity rate of 1% and mortality rate of 0.05%, or VATS, with an associated morbidity rate of 4% and mortality rate of 2% (8,32).…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating mediastinal lymphadenopathy for sarcoidosis, potential diagnostic tools include mediastinoscopy and endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) (7). Though mediastinoscopy is the gold standard for evaluating mediastinal lymphadenopathy of unknown etiology, it requires general anesthesia and has associated risks including recurrent laryngeal nerve injury, bleeding, and tracheal injury (8).…”
Section: Introductionmentioning
confidence: 99%